The mitochondrial tRNA(Ala) T5628C variant may have a modifying role in the phenotypic manifestation of the 12S rRNA C1494T mutation in a large Chinese family with hearing loss - Han, Dongyi; Dai, Pu; Zhu, Qingwen; Liu, Xin; Huang, Deliang; Yuan, Yongyi; Yuan, Huijun; Wang, Xinjian; Qian, Yaping; Young, Wie-Yen; Guan, Min-Xin (Biochemical and biophysical research communications, 2007)
We report here the clinical, genetic, and molecular characterization of a large Han Chinese family with aminoglycoside-induced and nonsyndromic hearing loss. Two and 13 of 66 matrilineal relatives suffered from aminoglycoside-induced and nonsyndromic hearing loss, respectively. These matrilineal relatives exhibited a wide range of severity of hearing loss, varying from profound to normal hearing. In the absence of aminoglycosides, the age-at-onset of hearing impairment in these matrilineal relatives ranged from 13 to 50years. Furthermore, these affected matrilineal relatives shared some common features: bilateral hearing loss of high frequencies and symmetries. Sequence analysis of mitochondrial DNA (mtDNA) in the pedigree identified the homoplasmic 12S rRNA C1494T mutation and other 34 variants belonging to Eastern Asian haplogroup F1. Of these, the variant T5628C occurs at an extremely conserved nucleotide (A31) of tRNA(Ala). This variant converted a very conservative A-U to a G-U base-pairing at AC-stem of this tRNA. The disruption of this base-pairing in tRNAs by mtDNA mutations has been associated with several clinical abnormalities. The alteration of structure of the tRNA(Ala) by the T5628C mutation may lead to a failure in tRNA metabolism and lead to impairment of mitochondrial translation, thereby worsening mitochondrial dysfunctions, caused by the C1494T mutation. Therefore, this mtDNA mutation may influence the phenotypic manifestation of the 12S rRNA C1494T mutation in this Chinese pedigree.